2019
DOI: 10.1002/hbm.24885
|View full text |Cite
|
Sign up to set email alerts
|

Post‐stroke cognitive deficits rarely come alone: Handling co‐morbidity in lesion‐behaviour mapping

Abstract: Post‐stroke behavioural symptoms often correlate and systematically co‐occur with each other, either because they share cognitive processes, or because their neural correlates are often damaged together. Thus, neuropsychological symptoms often share variance. Many previous lesion‐behaviour mapping studies aimed to methodologically consider this shared variance between neuropsychological variables. A first group of studies controlled the behavioural target variable for the variance explained by one or multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…However, associations in neuropsychological data are ambiguous, which is why neuropsychology focussed on the dissociation method for such a long time. This is in line with a study that found that lesion mapping of components obtained from neuropsychological data can result in artefacts (Sperber, Nolingberg & Karnath, 2020).…”
Section: Introductionsupporting
confidence: 91%
“…However, associations in neuropsychological data are ambiguous, which is why neuropsychology focussed on the dissociation method for such a long time. This is in line with a study that found that lesion mapping of components obtained from neuropsychological data can result in artefacts (Sperber, Nolingberg & Karnath, 2020).…”
Section: Introductionsupporting
confidence: 91%
“… 26 Neither strategy yielded significant results that survived FDR correction. A possible reason for these null findings is that covariate control can mislead judgements about causal relations 37 , 38 and might control away the very effects we wanted to measure in the first place.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this point reflects a general limitation of lesion-behaviour mapping, 24 which is not necessarily overcome by covariate control. 37 However, the complementary use of neuroscientific methods has the potential to alleviate this issue. 78 Third, the present sample was tested in the chronic post-stroke stage at least several months after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be assumed that the analysis indeed significantly reflects the anatomy of apraxia. Notably, this point reflects a general limitation of lesion-behaviour mapping 27 , which is not necessarily overcome by covariate control 62 . However, the complementary use of neuroscientific methods has the potential to alleviate this issue 63 .…”
Section: Limitationsmentioning
confidence: 99%